Bank pay caps, bank risk, and macroprudential regulation - Thanassoulis, J (University of Oxford, 2012)
This paper studies the consequences of a regulatory pay cap in proportion to assets onbank risk, bank value, and bank asset allocations. The cap is shown to lower banks' riskand raise banks' values by acting against a competitive externality in the labour market.The risk reduction is achieved without the possibility of reduced lending from a Tier 1increase. The cap encourages diversi cation and reduces the need a bank has to focus ona limited number of asset classes. The cap can be used for Macroprudential Regulationto encourage banks to move resources away from wholesale banking to the retail bankingsector. Such an intervention would be targeted: in 2009 a 20% reduction in remunerationwould have been equivalent to more than 150 basis points of extra tier 1 for UBS, forexample.